MENINGKATKAN KEMAMPUAN BERHITUNG PESERTA DIDIK MELALUI METODE JARIMATIKA PADA KELAS III UPT SPF SD INPRES MINASA UPA KOTA MAKASSAR: Penelitian Tindakan Kelas - Rezki Suhailah; Haerul Syam; Ahmad Syamsuadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Students' numeracy skills are still relatively low. This can be seen when many students in their multiplication test have not answered the questions given and this is because students still do not understand the concept of multiplication. which is set. The purpose of this study is to Improve Students' Numeracy Skills Through the Jarimatika Method of Class III UPT SPF SD Inpres Minasa Upa Makassar City. This study was conducted with classroom action research (PTK). The subjects of the study were 19 students of class III UPT SPF SD Inpres Minasa Upa Makassar City. Data collection techniques were observation, testing (evaluation) and documentation. The data obtained were analyzed using quantitative and qualitative descriptive analysis. The results of the research achieved quantitatively are: (1) In cycle I, the average value of the arithmetic results of class III students of UPT SPF SD Inpres Minasa Upa was 65, (2) In cycle II, the average value of class III students of UPT SPF SD Inpres Minasa Upa was higher, reaching 92. The learning completion of class III students of UPT SPF SD Inpres Minasa Upa increased. In cycle I, 12 (63%) students achieved learning completion, while in cycle II, 19 (100%) students achieved learning completion and classical learning completion was achieved. Based on this, learning completion in cycle II was achieved classically, because the number of students who completed it reached 80%. So it can be concluded that the mathematics learning outcomes of class III students of UPT SPF SD Inpres Minasa Upa, Makassar City can be improved through the jarimatika method strategy.